Peasant and popular feminism: a history of collective constructions - Michela Katiuscia Alves dos Santos Calaça; Isaura Isabel Conte; Catiane Cinelli (Universidade Federal do Norte do Tocantins, 2018)
The following article describes and analyses the process of construction of the Peasant Popular Feminism in the Peasant Women's Movement (MMC), a new subject of academic studies. The methodology used is participatory action research, given the direct immersion of the authors in said movement for more than fifteen years. As part of the results of this immersion, we have three Master's dissertations (Conte, 2011; Cinelli, 2012; Santos, 2012) and two Doctorate's theses (Conte, 2014; Cinelli, 2016). Furthermore, the authors were involved in the process of debating the Peasant Popular Feminism in MMC for the past three years. We highlight the relevance of the fact that the Peasant Popular Feminism is fruit of the collective identity of the fighting MMC women. Above all, it is constructed in dialogue with other peasant's organizations of working women and feminists, in the defense of agroecology and freedom/liberation, and hoping to build a fair and solidary, that is to say, socialist society.